A Chaotic System Based Image Encryption Algorithm using Plaintext-related Confusion - Yong Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A new plaintext-related image encryption system based on the hyper-chaotic Lorenz system is proposed in this paper. In the proposed image encryption system, the hyper-chaotic Lorenz system is employed to generate six pseudo-random matrixes, where, two of them use the “add-modulus” operations to carry out the plaintext-unrelated image diffusion, and the other four matrixes are used to confuse the plaintext-related image. In the image confusion, each pixel will swap its location with another pixel, and the target location is determined by some elements in the plain image and the four matrixes. The proposed image encryption system can resist the chosen/known plaintext attacks due to the application of the plaintext-related image confusion in it. The simulation results show that the proposed encryption system also have the characters of fast encryption/decryption speed, large key space, strong key sensitivity, strong plaintext sensitivity, good statistical properties of cipher images, and large information entropy, etc. Thus, the proposed system can be used in practical communications.